Vaccinations and public concern in history : legend, rumor, and risk perception - Kitta, Andrea, 1977- (New York : Routledge, 2012)
"In spite of the success of the childhood inoculation movement, questions have persisted about the safety and efficacy of vaccines. Arguments such as the relationship between the MMR vaccine and autism have led to an alarming increase in the number of parents choosing to not vaccinate their children. Yet the evidence in favor of vaccination is very strong if one examines the recent inoculation history of countries such as Great Britain, Sweden, and Japan. A decline in the numbers of children vaccinated in these countries has had immediate effects. In Great Britain for example, over 10,000 cases of pertussis and thirty-six deaths were reported following a decrease in vaccination rates in 1974-1978. These studies, taken as a group, present a powerful argument for the need to understand reasons for vaccination reluctance. Vaccinations and Public Concern in History explores vernacular beliefs and practices that surround decisions not to vaccinate, with the primary aim of providing concrete recommendations for improving inoculation promotion programs and guidelines for physician interaction with inoculation resistant patients. Through the use of ethnographic, media, and narrative analyses, this book explores the vernacular explanatory models used in inoculation decision-making. The research on which the book draws was designed to help create public health education programs and promotional materials that respond to patients fears, understandings of risk, concerns, and doubts. Exploring the nature of inoculation distrust and miscommunication, Andrea Kitta identifies areas that require better public health communication and greater cultural sensitivity in the handling of inoculation programs"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Vaccination -- Complications; Health attitudes; Vaccination -- History; Electronic books